Artificial dry surface biofilm models for testing the efficacy of cleaning and disinfection. (1st April 2019) - Ledwoch, K.; Said, J.; Norville, P.; Maillard, J.‐Y.
Abstract: Dry surface biofilms (DSB) harbouring pathogens are widespread in healthcare settings, are difficult to detect and are resistant to cleaning and disinfection interventions. Here, we describe a practical test protocol to palliate the lack of standard efficacy test methods for DSB. Staphylococcus aureus DSB were produced over a 12‐day period, grown with or without the presence of organic matter, and their composition and viability were evaluated. Disinfectant treatment was conducted with a modified ASTM2967‐15 test and reduction in viability, transferability and biofilm regrowth post‐treatment were measured. Dry surface biofilms produced over a 12‐day period had a similar carbohydrates, proteins and DNA content, regardless of the presence or absence of organic matter. The combination of sodium hypochlorite (1000 ppm) and a microfiber cloth was only effective against DSB in the absence of organic load. With the increasing concerns of the uncontrolled presence of DSB in healthcare settings, the development of effective intervention model in the presence of organic load is appropriate for the testing of biocidal products, while the use of three parameters, log10 reduction, transferability and regrowth, provides an accurate and practical measurement of product efficacy. Significance and Impact of the Study: The widespread presence of biofilms on dry surfaces in healthcare settings has been recently documented. These dry surface biofilms (DSB) present an unprecedented challenge to cleaning and disinfection processes. Here, we describe a practical efficacy protocol based on an in vitro Staphylococcus aureus DSB model. The protocol measures reduction in viability, transferability and biofilm regrowth post‐treatment to provide altogether a practical assessment of product efficacy against dry surface biofilms.